Effect of renewable energy sources integration on the optimal coordination of directional over-current relays in distribution system - Lazhar Bougouffa; Abdelaziz Chaghi (Institute of Advanced Engineering and Science, 2020)
The demand for power electricity is growing fast and one of the main tasks for power engineers is to generate electricity from renewable energy sources (RES). Nevertheless, problems arise when the new generation is integrated in the power distribution network. Under this condition, the main purpose in this paper, an investigation of the effect of RES integration on the optimal coordination of directional over-current relays in distribution system, a dual simplex optimization algorithm has been presented to determine the coordination of directional over-current relays (DOCRs). The system used to check the efficiency of the optimization algorithm which is IEEE 33-bus models. The analysis is performed in MATLAB software environment.